PERANCANGAN APLIKASI BRANDQU MENGGUNAKAN KONSEP OPERASIONAL MANAJEMEN HUBUNGAN PELANGGAN - Lilian; Fadilah Najwa, Nina (Jurnal Sistem Informasi dan Bisnis Cerdas, 2025)
The BrandQu application is a media and idea that emerged due to seeing the development of digitalization of product marketing carried out by many business through influencer marketing. From the 3 categories of operational dimensions, (customer relationship management) it is identified which features suit user needs for the BrandQu application. The sprint design method was used as a tool to validate the features created. The results of the sprint design obtained 5 service automation features, namely case management, customer self service, scheduling, inbound communication management and payment management. There are 4 sales force automation features, namely customer segmentation, account management and sales management. There are 5 marketing automation features, namely trigger marketing and loyalty management. This research produced a prototype which was tested in two iterations using task completion and single ease question. The results of the single ease question have an average of 5.6, which means that the design of Operational CRM features is easy for users to use. The results of usability testing from these four aspects are worth more than 81% which can be concluded that the appearance of the high-fidelity prototype is very good.